RELATIONSHIPS BETWEEN ENVIRONMENTAL FACTORS AND PLANT FUNCTIONAL TRAITS IN MANGROVE ECOSYSTEMS: CHARACTERIZATION BY - Francisco Cadena Cadena; Jony R Torres; Iram Mondaca-Fernández; Joe Luis Arias-Moscoso; Leandris Argentel Martinez; Francisco Javier Choix Ley (Journal of Animal and Plant Sciences, 2025)
Mangrove ecosystems are of crucial importance in maintaining biodiversity and environmental stability. However, these ecosystems are increasingly threatened by anthropogenic and natural factors. The implementation of conservation strategies that take advantage of the unique functional traits of mangroves is therefore essential for their protection. This study employs the technique of Fourier transform infrared spectroscopy (FT-IR) to analyze the relationship between environmental factors and the functional properties of the leaves of white mangrove (Laguncularia racemosa), black mangrove (Avicennia germinans) and red mangrove (Rhizophora mangle). This analysis provides biochemical fingerprints that reveal the influence of environmental factors on ecosystem functioning, with significant correlations found between spectral bands and environmental variables. Temperature exhibited a correlation with band 1 (3323-3398 cm-1), linked to carbohydrates, proteins, alcohols and phenolic compounds. Salinity and bulk density influenced bands 3 (1717-1729 cm-1) and 4 (1614-1655 cm-1), associated with amide I, pectin, phospholipids and cholesterol esters. The influence of surface soil pH on band 7 (1130-1165 cm-1) reflected the presence of polysaccharides, while subsoil pH aligned with band 6 (1203-1237 cm-1), indicative of lignin and xylans. Furthermore, an association was observed between organic matter content and bands 5 (1462 cm-1) and 8 (999-1103 cm-1), indicating the role of cellulose and pectin in cell structure. Additionally, interstitial soil pH influenced bands 9 (815-884 cm-1) and 10 (719 cm-1), linked to cellulose and amide V stability, respectively. The findings demonstrate the significant impact of environmental factors (temperature, salinity and pH) on the chemical composition of mangrove ecosystems, and the results provide fundamental information on their biochemical adaptations. This supports the development of conservation strategies to improve the resilience and sustainability of these ecosystems.
Keywords: mangrove; environmental changes; FT-IR